Development of an angle sensor using optical polarizer - Rana, M. M.; Mohd Razib, Mohd Ashraf; Saleh, Tanveer; Abdul Muthalif, Asan Gani (Asian Research Publishing Network (ARPN), 2015)
This paper presents an effective technique to measure angle of rotation using optical polarizer. In this case combination of single wavelength partially polarised laser beam and a linear polarizer are used for the rotational angle measurement. The power of the transmitted partially polarized light was found varied according to the angle variation of the polarizer. This concept can be used to sense the angle of rotation. High and low measurement of the transmitted power was obtained at 90º interval for the entire range of angle 180°. To ensure the precision, accuracy and reliability of the sensor, the experiments were repeated and error percentage was captured in accordance of predicted model. From all experimental investigations, it has been concluded that varying the output power according to the polarizer’s angle rotation could be an indicator to an angle successfully. The experiment was conducted using polarized laser source, iris, attenuator, polarizer and a photo detector to measure the transmitted polarized power coming through a polarizer. The major advantages of this type of angle sensor are its compact size, cost effectiveness, passive type without extra circuit, no effect of electromagnetic noise and flexibility in using at long distance.